Palliative procedures for malignant gastric outlet obstruction: a network meta-analysis - Tran, Khoi Van; Vo, Nguyen-Phong; Nguyen, Hung Song; Vo, Nhi Thi; Thai, Thi Bao Trang; Pham, Vu Anh; Loh, El-Wui; Tam, Ka-Wai (Endoscopy, 2024)
Background The optimal treatment for malignant gastric outlet obstruction (GOO) remains uncertain. This systematic review aimed to comprehensively investigate the efficacy and safety of four palliative treatments for malignant GOO: gastrojejunostomy, endoscopic ultrasound-guided gastroenterostomy (EUS-GE), stomach-partitioning gastrojejunostomy (PGJ), and endoscopic stenting.Methods We searched PubMed, Embase, Cochrane Library, Scopus, and Web of Science databases, ClinicalTrials.gov, and the World Health Organization International Clinical Trials Registry Platform for randomized controlled trials (RCTs) and cohort studies comparing the four treatments for malignant GOO. We included studies that reported at least one of the following clinical outcomes: clinical success, 30-day mortality, reintervention rate, or length of hospital stay. Evidence from RCTs and non-RCTs was naïve combined to perform network meta-analysis through the frequentist approach using an inverse variance model. Treatments were ranked by P score.Results This network meta-analysis included 3617 patients from 4 RCTs, 4 prospective cohort studies, and 32 retrospective cohort studies. PGJ was the optimal approach in terms of clinical success and reintervention (P scores: 0.95 and 0.90, respectively). EUS-GE had the highest probability of being the optimal treatment in terms of 30-day mortality and complications (P scores: 0.82 and 0.99, respectively). Cluster ranking to combine the P scores for 30-day mortality and reintervention indicated the benefits of PGJ and EUS-GE (cophenetic correlation coefficient: 0.94; PGJ and EUS-GE were in the same cluster).Conclusion PGJ and EUS-GE are recommended for malignant GOO. PGJ could be the alternative choice in centers with limited resources or in patients who are unsuitable for EUS-GE.